Application of modern technology in the study of hadith and its sciences: A case study - Chowdhury M.H.; Rab M.A.A.; Said W.M.; Ghazali N.M.; Mohamed Y.; Toure A.K. (American Scientific Publishers, 2024)
Indexed by Scopus/ERA